The Culture of Safe Vital Activity at the Personality in Human Development. (Journal of Educational Sciences, 2017)
To understand the phenomenon of the «culture of safe live and activity» the article describes the concepts that are part of it and provide a basis:culture, life and activity, safety. It analyzed the concept of «culture», which depends on the scientific field in which attempts to clarify its nature. A human came out of nature, it is a part of it, but it is not limited. Human creates new in his activities, and that is called culture, and where nature creativity ends, creativity of culture begins. Life activity is an activity that insures the person as an individual. Man as an individual trying to send their life activity for survival, the satisfaction of physiological needs; people-person for this operation adds to creation of his being, the environment, living conditions, communication, education, labor, culture. Safety – is the absence (not create) the circumstances and situations that could cause harm, loss, negative impact on human well-being (physical, mental, social, financial, environmental and others.). The analysis indicated that the culture of safe life and activity – it is a complex, multi-level, dynamic phenomenon, which includes cognitive, activity-operative, personality-value components.
Keywords: culture; security; life and activity; culture of safe live and activity